Tradisi Penyerahan Perabot Rumah Tangga Pada Perkawinan Dalam Perspektif Hukum Islam - Umar Faruq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
Marriage is one of the many religious rituals carried out with the aim of creating a family. In rural communities that are full of traditional values, marriage is not only carried out according to procedures or regulations in accordance with religious regulations. In this case it is the Islamic religion. One of the most important things in organizing a marriage is the presence of a dowry. The dowry is identical to the binding of the groom to the bride who becomes his wife. Islamic law does not set a limit on the amount of the dowry, because the most important thing is the wife's acceptance of her husband's gift. Karduluk village, which was the location of this research, gave dowries in the form of household items ranging from cupboards, cots/beds, chairs and tables, decorative cupboards, and so on. These items are brought to the bride's house during the wedding and are considered part of the dowry.